2016
DOI: 10.1039/c5nr07267k
|View full text |Cite
|
Sign up to set email alerts
|

A miniaturized microbial fuel cell with three-dimensional graphene macroporous scaffold anode demonstrating a record power density of over 10 000 W m−3

Abstract: A microbial fuel cell (MFC) is a bio-inspired renewable energy converter which directly converts biomass into electricity. This is accomplished via the unique extracellular electron transfer (EET) of a specific species of microbe called the exoelectrogen. Many studies have attempted to improve the power density of MFCs, yet the reported power density is still nearly two orders of magnitude lower than other power sources/converters. Such a low performance can primarily be attributed to two bottlenecks: (i) inef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
69
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(76 citation statements)
references
References 62 publications
3
69
3
1
Order By: Relevance
“…It should be noted that the electron producing capability of strain MR-1 used in our device has limited the output current and power density. By using optimally mixed bacterial cultures, such as Geobacteraceae -enrichment cultures1952, the electricity generation capability of the device could be further enhanced. Table 2 also compares the CE values of our FT with non-FT devices calculated based on the consumption of 20 mM lactate in the lactate defined minimal medium when the devices operated in batch mode (see the calculation method in Experimental section).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted that the electron producing capability of strain MR-1 used in our device has limited the output current and power density. By using optimally mixed bacterial cultures, such as Geobacteraceae -enrichment cultures1952, the electricity generation capability of the device could be further enhanced. Table 2 also compares the CE values of our FT with non-FT devices calculated based on the consumption of 20 mM lactate in the lactate defined minimal medium when the devices operated in batch mode (see the calculation method in Experimental section).…”
Section: Resultsmentioning
confidence: 99%
“…It has been utilized in electronic devices272829, energy storage and conversion devices3233343536373839404142, and neural tissue engineering495051. Recently, GF, with the pore size of a few hundred micrometers, has also been employed as anode material of MFCs and demonstrated that the scaffold of GF is favorable for bacteria colonization and electron transfer27293052. It should be noted that all the existing GF-based MFCs adopted a traditional non-FT design where the nutritional media flow over the anode.…”
mentioning
confidence: 99%
“…When selecting the electrode materials for bio-electro-Fenton microbial fuel cells, the anode materials should have (1) good conductivity and low impedance; (2) excellent biocompatibility; (3) stable chemical properties; (4) good corrosion resistance; and (5) good mechanical properties [7,8,9,10]. The cathode electrode needs to have good electrochemical properties because a strong oxidation-reduction ability may be conducive to electron transport.…”
Section: Introductionmentioning
confidence: 99%
“…We have demonstrated miniaturized MFCs and microbial supercapacitors with record power densities of 1. [5,7,20]. In this paper, we report the first study of temperature effect on a miniaturized MFC with Geobacter dominated mixed species.…”
Section: Introductionmentioning
confidence: 99%
“…During the past two decades, significant improvement on MFC has been demonstrated; for instance, the power density of microbial fuel cells have improved by more than four orders of magnitude, from 0.1 mWm −2 to 7.72 Wm −2 [4][5][6]. In order to improve the power density, a number of research have been performed, such as implementing the anode with high surface area to volume ratio [5,[7][8][9], investigating the performance of different species of exoelectrogen [10,11], investigating different MFC configurations, and investigating different operation conditions, including temperature, pH, flow rate, etc. [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%